2018
DOI: 10.3389/fphys.2018.00719
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal Asynchrony Contributes to Exercise Limitation in Mild Asthmatic Subjects

Abstract: This study aimed to better understand how subjects with stable asthma and without exercise-induced bronchoconstriction respond to mild exercise. Breathing pattern, chest wall compartmental and operational volumes, and thoracoabdominal asynchrony were assessed in 11 stable asthmatic subjects and 10 healthy subjects at rest and during exercise in a cycle-ergometer through optoelectronic plethysmography. Dyspnea and sensation of leg effort were assessed through Borg scale. During exercise, with similar minute ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…For asynchronous analysis, the inspiratory paradox time (IPT) and expiratory paradox time (EPT) of the upper RC, lower RC, and ABD were also calculated. These parameters were defined as the fraction of time relative to the total chest wall displacement signal (expressed as percentage), in which the compartmental signals decreased during inspiration (IPT) and increased during expiration (EPT) 25 , 26 , 28 , 29 .…”
Section: Methodsmentioning
confidence: 99%
“…For asynchronous analysis, the inspiratory paradox time (IPT) and expiratory paradox time (EPT) of the upper RC, lower RC, and ABD were also calculated. These parameters were defined as the fraction of time relative to the total chest wall displacement signal (expressed as percentage), in which the compartmental signals decreased during inspiration (IPT) and increased during expiration (EPT) 25 , 26 , 28 , 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Phase-angle or thoraco-abdominal asynchrony has been used to assess respiratory function in children [ 6 , 7 , 27 ] and adults [ 8 , 28 ]. Based on our data, TAA is high and variable during early life and reduces in both magnitude and variability with age.…”
Section: Discussionmentioning
confidence: 99%
“…A higher TAA in the supine position compared to seated is shown in M ayer et al [ 29 ]. TAA in healthy subjects in a seated position is reported elsewhere [ 28 , 30 ]. The number of healthy subjects is low (n=10 and n=9 at rest, respectively), and the method for calculation of phase differs slightly from what has been used herein.…”
Section: Discussionmentioning
confidence: 99%
“…F regonezi et al . [93] carried out a study to ascertain whether chest wall and compartmental volume responses differ between mild asthmatic patients and healthy subjects. The study demonstrated that during mild exercise, asthma patients adopted a different breathing pattern to healthy individuals that was characterised by rapid shallow breathing, existence of end-expiratory chest wall dynamic hyperinflation, and thoraco-abdominal asynchrony between the rib cage and abdominal chest compartments.…”
Section: Mechanisms That Underlie Exercise Limitation In Various Respmentioning
confidence: 99%